2016
DOI: 10.1016/j.fertnstert.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the needs of fertility treatment patients and their partners: are they informed of and do they receive mental health services?

Abstract: Psychological distress is common during fertility treatment, but most patients and partners do not receive and are not referred for MHS. Furthermore, MHS use and referral is not targeted to those at high risk for serious psychological distress. More attention needs to be given to the mental health needs of our patients and their partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 34 publications
4
82
2
3
Order By: Relevance
“…Yet maternal depressive symptoms, whether occurring during pregnancy or culminating in the postpartum period, are a common and major contributor to maternal morbidity and mortality (8). Furthermore, psychologic distress is, unsurprisingly, associated with subfertility (9), and several studies show a high prevalence of anxiety and depression among couples undergoing IVF (9)(10)(11). Treatment failures are particularly linked to psychologic distress (12), but even successful IVF mothers may experience a complex transition to parenthood with intense fetal attachment and anxiety (13)(14)(15).…”
mentioning
confidence: 99%
“…Yet maternal depressive symptoms, whether occurring during pregnancy or culminating in the postpartum period, are a common and major contributor to maternal morbidity and mortality (8). Furthermore, psychologic distress is, unsurprisingly, associated with subfertility (9), and several studies show a high prevalence of anxiety and depression among couples undergoing IVF (9)(10)(11). Treatment failures are particularly linked to psychologic distress (12), but even successful IVF mothers may experience a complex transition to parenthood with intense fetal attachment and anxiety (13)(14)(15).…”
mentioning
confidence: 99%
“…According to some recent results [55,58] A recent meta-analysis [6] of 14 studies indicated that although distress appears not to compromise the possibility of becoming pregnant in women undergoing fertility treatment, contrary to what many couples believe, definitive research is lacking and the relation is complex.…”
Section: Optimism and Resilience In Infertilitymentioning
confidence: 99%
“…Such psychological problems may occur when it is impossible to conceive a child naturally and after unsuccessful IVF attempts (Filippova, 2009;Hynes, Callan, Terry, & Gallois, 2011). One or both partners (spouses) may have a depressed mood, decreased energy, and low general well-being (Haimovici et al, 2018;Maroufizadeh, Karimi, Vesali, & Omani Samani, 2015;Pasch et al, 2016;Williams, Marsh, & Rasgon, 2007). Negative emotions of people suffering from infertility can also be accompanied by negative self-perception, a negative and inconsistent self-image, and self-blame, which can negatively affect family life satisfaction (Filippova, 2009;Greil, Slauson-Blevins, & McQuillan, 2010).…”
Section: Psychological States Of Spouses During Ivf Treatmentmentioning
confidence: 99%